2021
DOI: 10.26534/kimika.v32i1.34-45
|View full text |Cite
|
Sign up to set email alerts
|

Experimenting on Natural Acid-Base Indicators: A Home-based Chemistry Activity during the COVID-19 Pandemic as evaluated by Teachers

Abstract: This study determined the feasibility of conducting a laboratory experiment on natural acid-base indicators as a home-based activity. Seven high school teachers from Cebu in Central Visayas, Philippines conducted the home-based activity, evaluated the activity using a validated questionnaire, and were interviewed for opportunities and challenges. Results showed that the at-home activity was feasible and satisfactory, however inaccuracies and inconsistencies were found in the results of the experiment. Neverthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
1
3
0
3
Order By: Relevance
“…In turn, the study of Dioneda (2019) has the largest effect size, at g=3.94, which means that a student exposed to localized and contextualized teaching improved their biology performance to a greater extent than the control group. These quantitative studies are supported by the other Philippine studies on using contextualization in science (Belen & Caballes, 2020;Sanchez et al, 2021;Tabotabo-Picardal & Picardal, 2017;Tadena & Hairulla, 2021), which indicates that the instructional approach investigated by the meta-analysis has a positive effect on science learning.…”
Section: Effect Sizes Of Contextualized Instruction In Sciencesupporting
confidence: 69%
See 1 more Smart Citation
“…In turn, the study of Dioneda (2019) has the largest effect size, at g=3.94, which means that a student exposed to localized and contextualized teaching improved their biology performance to a greater extent than the control group. These quantitative studies are supported by the other Philippine studies on using contextualization in science (Belen & Caballes, 2020;Sanchez et al, 2021;Tabotabo-Picardal & Picardal, 2017;Tadena & Hairulla, 2021), which indicates that the instructional approach investigated by the meta-analysis has a positive effect on science learning.…”
Section: Effect Sizes Of Contextualized Instruction In Sciencesupporting
confidence: 69%
“…Finally, the aim of this current investigation is reporting on the curriculum, enacted vis-à-vis contextualized instruction, and described by empirical studies conducted by teachers and researchers in the Philippines. The extent of effectiveness of contextualization is gauged through analysis of studies undertaken in various scientific disciplines, such as biology (Belen & Caballes, 2020;Tabotabo-Picardal & Paño, 2017), chemistry (Sanchez, 2017(Sanchez, , 2021, physics (Rivera & Sanchez, 2020), environmental science (Tadena & Salic-Hairulla, 2021), and home-based experimentation (Sanchez et al, 2021). The popularity of the contextualization approach as an instructional intervention warrants further investigation into the extent of its effectiveness in helping students achieve learning outcomes, as do the various strategies employed in contextualization instruction.…”
Section: Contextualization In the Context Of The Studymentioning
confidence: 99%
“…Several difficulties emerged during the implementation such as the lack of practical activities and the poor quality of instructional materials. Sanchez et al (2021) performed a study to determine the feasibility of conducting a laboratory experiment on natural acid-base indicators as a home-based activity. They found that although at-home activities are feasible and satisfying, there were errors and discrepancies in the outcomes of the experiments.…”
Section: Theoretical Framework Of the Studymentioning
confidence: 99%
“…Indikator yang digunakan dalam titrasi menunjukkan perubahan warna yang ditandai dengan baik dalam interval pH tertentu, Sebagian besar indikator ini adalah pewarna organik dan berasal dari sintetik tetapi karena menimbulkan pencemaran lingkungan, aspek ketersediaan dan biaya, maka pencarian senyawa alami sebagai indikator asam basa dimulai [2]. Beberapa peneliti sudah memanfaatkan potensi pewarna alami untuk indikator asam basa [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Pendahuluanunclassified
“…Media pembelajaran yang dapat merangsang cara berpikir siswa salah satunya adalah dengan memanfaatkan sumber daya alam sekitar. Penerapan teknologi pembelajaran, yaitu dengan memberdayakan sumber-sumber belajar yang dirancang dan dimanfaatkan serta dikelola untuk tujuan pembelajaraan seperti memanfaatkan sumber daya alam sekitar, dapat meningkatkan pemahaman siswa [5,10].…”
Section: Analisis Situasiunclassified